PEMBELAJARAN FIKIH DAN PERKEMBANGANNYA UNTUK SISWA KELAS X MA SWASTA ALHAKIMIYAH PARINGGONAN DENGAN METODE PENELITIAN TINDAKAN KELAS - Harahap, Muhammad Yusuf (PANTAK: Jurnal Penelitian Tindakan Kelas, 2024)
This research aims to improve the understanding of class X students of MA Alhakimiyah Paringgonan towards Fiqh material through the application of the Classroom Action Research (PTK) method. The problems faced in learning Fiqh in class X are students' low understanding of the basic concepts of Fiqh and difficulties in applying Islamic religious teachings in daily life. This research was carried out in three cycles, each of which consisted of four stages: planning, action, observation, and reflection. The first cycle showed that only 45% of students achieved the Minimum Completeness Criteria (KKM) in the final test, which indicates the low understanding of students of Fiqh material. In the second cycle, with the application of project-based methods and group discussions, there was a significant increase, with 70% of students achieving KKM. In the third cycle, with the addition of simulation of worship practices and peer teaching, 85% of students managed to achieve KKM. These results indicate a significant increase in students' understanding of Fiqh material after the implementation of PTK. Overall, this study concludes that the use of the PTK method with a project-based approach, discussion, and simulation is very effective in increasing the understanding of class X students of Fiqh material, as well as providing a more applicable and meaningful learning experience for students.